Added Value of QuantiFERON TB-Gold in-Tube for Detecting Latent Tuberculosis Infection among Persons Living with HIV/AIDS. (29th May 2014) - Souza, Josiane Maria Oliveira; Evangelista, Maria do Socorro Nantua; Trajman, Anete
Abstract : Objective . To evaluate the added value of QuantiFERON TB-Gold in-Tube (QTF-GIT) over the tuberculin skin testing (TST) for detecting latent tuberculosis (TB) infection (LTBI) among patients with AIDS in a city with a low TB incidence rate (11.1/100, 000 inhabitants) and universal BCG coverage. Methods . Three hundred consecutive patients with AIDS in eight outpatient sexually transmitted disease public clinics in Brasilia were submitted to QFT-IT and TST between May 2011 and March 2013. A positive result of either test was considered to be LTBI. Results . Median CD4-cell count was 477.5 cells/mm 3 ; 295 (98.3%) were using antiretroviral therapy. Eighteen patients (6%, 95% CI: 3.6%–9.3%) had LTBI, of whom 4 (1.3%, 95% CI: 0.04%–2.63%) had only a positive TST, 8 (2.7%, 95% CI: 0.8%–4.5%) had only a QFT-GIT positive test, and 6 (2%, 95% CI: 0.4%–3.6%) had positive results for both tests. This represents an 81.8% relative increase in LTBI detection when QFT-GIT is added to TST. The concordance between both tests was 96% (k = 0.48 ). Conclusions . The QFT-GIT alone was more effective to detect LTBI than TST alone and had an 81% added value as an add-on sequential test in this population with mild immunosuppression. The cost-effectiveness of these strategies remains to be evaluated.